Correction: Transcriptomic changes behind Sparus aurata hepatic response to different aquaculture challenges: An RNA-seq study and multiomics integration. - Cláudia Raposo de Magalhães; Kenneth Sandoval; Ferenc Kagan; Grace McCormack; Denise Schrama; Raquel Carrilho; Ana Paula Farinha; Marco Cerqueira; Pedro M Rodrigues (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300472.].